Circular Economy Education Through Food Preparation as an Effort to Reduce Food Waste and Strengthen the Family Economy - Suasih, Ni Nyoman Reni; Saskara, Ida Ayu Nyoman; Dewi, Made Heny Urmila; Purwanti, Putu Ayu Pramitha; Tisnawati, Ni Made; Saraswati, I Gusti Ayu Prili; Saskara, Ida Ayu Gde Dyastari (International Journal of Research in Community Services, 2024)
Circular economy literacy efforts are important considering that the waste awareness index in Indonesia is still worrying. If we look at the data from the National Waste Management Information System (SIPSN), food waste dominates the composition of waste based on waste type, namely 40.2 percent. When looking at the source, it is known that households are the largest source of waste (38.3 percent). Considering these data and facts, preventive efforts need to be carried out at the household level, especially regarding food waste. This activity aims to provide education for mothers regarding the circular economy and food waste behavior to minimize food waste, especially in its preparation or better known as food preparation. It is also believed that this effort will have a positive impact on the family's economy. This activity is carried out through the outreach method, and is also accompanied by a pre-test and post-test as a form of evaluation. The locus of the activity will be carried out in Batuan Village, Sukawati District, Gianyar Regency, targeting the local village PKK (family welfare empowerment) team. The aim is that information and activity materials can be distributed and implemented widely. After comparing the results of the pre-test and post-test, it was discovered that there had been an increase in service participants' understanding of the circular economy and food preparation. It is certainly important to continue this activity, one of which is through assistance in preparing circular economy programs through the PKK.